Scanning Electrochemical Microscopy: Activity Mapping of Ascorbate Oxidase Immobilized onto Glass Surface - Ali Esmail Karim (Journal of Global Pharma Technology, 2018)
Glass-microscope slides were covalently modified with a common coupling agent of 3-aminopropyltriethoxysilane (APTES) by silanization reaction. After activated with glutaraldehyde, ascorbic oxidase was immobilized on microscope slides. The modified slides were examined before and after activation with glutaraldehyde by Fourier transform infrared spectroscopy (FTIR).The scanning electrochemical microscopy images of modified microscope slide have been used to detect the presence of the ascorbic acid oxidase as its confirm the direct electron transfer process in feedback mode experiments and provide that the enzyme is evenly immobilized on the modifies slide.Keywords: Catalytic activity, Ascorbate oxidase, Surface modification, APTES, Glutaraldehyde, SECM.